Intramyocardial implantation of differentiated rat bone marrow mesenchymal stem cells enhanced by TGF-β1 improves cardiac function in heart failure rats - Y. Lv; B. Liu; H.P. Wang; L. Zhang (Brazilian Journal of Medical and Biological Research, 2016)
The present study tested the hypotheses that i) transforming growth factor beta 1 (TGF-β1) enhances differentiation of rat bone marrow mesenchymal stem cells (MSCs) towards the cardiomyogenic phenotype and ii) intramyocardial implantation of the TGF-β1-treated MSCs improves cardiac function in heart failure rats. MSCs were treated with different concentrations of TGF-β1 for 72 h, and then morphological characteristics, surface antigens and mRNA expression of several transcription factors were assessed. Intramyocardial implantation of these TGF-β1-treated MSCs to infarcted heart was also investigated. MSCs were initially spindle-shaped with irregular processes. On day 28 after TGF-β1 treatment, MSCs showed fusiform shape, orientating parallel with one another, and were connected with adjoining cells forming myotube-like structures. Immunofluorescence revealed the expression of cardiomyocyte-specific proteins, α-sarcomeric actin and troponin T, in these cells. The mRNA expression of GATA4 and Nkx2.5 genes was slightly increased on day 7, enhanced on day 14 and decreased on day 28 while α-MHC gene was not expressed on day 7, but expressed slightly on day 14 and enhanced on day 28. Transmission electron microscopy showed that the induced cells had myofilaments, z line-like substances, desmosomes, and gap junctions, in contrast with control cells. Furthermore, intramyocardial implantation of TGF-β1-treated MSCs to infarcted heart reduced scar area and increased the number of muscle cells. This structure regeneration was concomitant with the improvement of cardiac function, evidenced by decreased left ventricular end-diastolic pressure, increased left ventricular systolic pressure and increased maximal positive pressure development rate. Taken together, these results indicate that intramyocardial implantation of differentiated MSCs enhanced by TGF-β1 improved cardiac function in heart failure rats.